Too many boats chasing too few fish - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 1999)
Last October, the government of Mauritania put a two month stop to fishing. The measure has been taken to ensure that fish stocks are preserved and can be replenished in a natural way. The country's decision coincides with an initiative taken at a...